2008
DOI: 10.1007/s00586-008-0596-y
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rotatory atlantoaxial dislocation without neurological compromise in a child with Down syndrome: a case report

Abstract: Spontaneous atlantoaxial dislocation is a rare recognised complication of Down syndrome. In the majority of cases, dislocation takes place in an anteroposterior direction and is often associated with abnormalities of odontoid development or ossification. Rotatory atlantoaxial dislocation is extremely rare in Down syndrome and this is to our knowledge the first reported case in which modern imaging methods have been described; surface shaded reformats derived from a multislice CT scan were of fundamental import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition to this metabolic predisposition to weight gain, children and adolescents with trisomy 21 have been shown to participate in less high‐intensity physical activity than their siblings (Whitt‐Glover et al ) and do not meet the recommended daily requirements of moderate to vigorous physical activity (Esposito et al ; Nordstrom et al ). Although there are valid medical reasons for the lower level of exercise, such as the risk of atlantoaxial subluxation or dislocation (Semine et al ; Au‐Yong et al ), unfortunately, environmental factors may also play a role in preventing regular participation in physical activity for individuals with intellectual disability. Heller et al () reported that many adults with trisomy 21 are unaware of opportunities for engagement in team sports or gym programmes within the community or may have difficulty with independent exercise and require the support, or participation, of family and friends.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this metabolic predisposition to weight gain, children and adolescents with trisomy 21 have been shown to participate in less high‐intensity physical activity than their siblings (Whitt‐Glover et al ) and do not meet the recommended daily requirements of moderate to vigorous physical activity (Esposito et al ; Nordstrom et al ). Although there are valid medical reasons for the lower level of exercise, such as the risk of atlantoaxial subluxation or dislocation (Semine et al ; Au‐Yong et al ), unfortunately, environmental factors may also play a role in preventing regular participation in physical activity for individuals with intellectual disability. Heller et al () reported that many adults with trisomy 21 are unaware of opportunities for engagement in team sports or gym programmes within the community or may have difficulty with independent exercise and require the support, or participation, of family and friends.…”
Section: Introductionmentioning
confidence: 99%
“…Atlantoaxial rotatory fixation (AARF) is an uncommon condition that usually occurs in children after an inflammatory upper respiratory tract infection or pharyngitis, but it can also be spontaneous or follow minor trauma or surgery on the oropharynx. 1 2 3 4 5 6 7 8 Fielding and Hawkins have classified AARF into four types on the basis of the rotational displacement and competency of the transverse ligament. 1 Most cases are thought to be the result of nonresolving acute atlantoaxial rotational subluxation or “acute torticollis.” Treatment usually consists of traction until reduction occurs, followed by immobilization in Minerva brace or halo vest.…”
Section: Introductionmentioning
confidence: 99%
“…Yong et al reported the successful use of halo traction to reduce AARS in a child with DS, Yamazaki et al could not achieve closed reduction with a halo vest in an adult with chronic AARS and resorted to open reduction with O-C3 fusion[11,15].…”
mentioning
confidence: 99%